Efficient Synthesis of Isoquinoline Derivatives through Sequential Cyclization–Deoxygenation Reaction of 2-Alkynylbenzaldoximes - Ayoubi, Mojtaba; Nikbakht, Ali; Amiri, Kamran; Abbasi Kejani, Alireza; Zahedian Tejeneki, Hossein; Balalaie, Saeed (SynOpen, 2022)
We describe a novel, simple, robust, and efficient cyclization/deoxygenation approach for the synthesis of functionalized isoquinoline derivatives. Over the course of continued studies on o-alkynylbenzaldoxime cyclization reactions, the formation of cyclic nitrones through 6-endo-dig cyclization was achieved using silver triflate or bromine as an electrophile, and subsequently, the deoxygenation process was carried out in the presence of CS2 in good to high yields.
Keywords: 2-alkynylbenzaldoxime; cyclization/deoxygenation; isoquinoline; silver triflate; bromine; carbon disulfide